Time‐lapse laboratory tests to monitor multiple phases of DNAPL in a porous medium. Issue 1 (18th December 2018) - Orlando, Luciana; Palladini, Lucia
ABSTRACT: A soil contaminated by dense non‐aqueous phase liquids generally exhibits variation of electrical permittivity and resistivity over time. In this paper, we relate photo images with results of electrical resistivity tomography, induced polarization tomography, and ground‐penetrating radar survey in a laboratory‐controlled test, where a cell, filled with grained‐glass beads contaminated with HFE‐7100 (hydrofluoroether) and under saturated conditions, was used. The aim was to find robust links between geophysical and physico‐chemical parameters of a contaminated soil in order to reduce the ambiguities in data interpretation. The monitoring, conducted over 100 days, shows that each geophysical method may or may not be sensitive to the multiple phases of hydrofluoroether (pure, dissolved and gaseous phases) depending on the contaminant (chemical composition, fresh, mature, etc.) and on the host enviroment. We propose some empirical relationships that allow us to quantitatively monitor the water saturation variation induced by hydrofluoroether. The photo images confirm that the pure phase of hydrofluoroether changes over time, which is probably due to biological or/and chemical variation of the contaminant. Electrical resistivity tomography results appear to be sensitive to the vast amount of pure phase of the hydrofluoroether. Induced polarization, measured in the extremely low frequency range (<25 Hz), allows detecting the pure phase of the contaminant, probably due to the decrease of water permeability and chemical degradation of the compound over time. The ground‐penetrating radar and time domain reflectometry methods based on measurements in very‐high frequency and ultra‐high frequency ranges are mainly sensitive to the water content and, as a consequence, to the replacement of water by pure and gaseous phases of hydrofluoroether.